2017
DOI: 10.1016/j.energy.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Darrieus wind turbine blade unsteady aerodynamics: a three-dimensional Navier-Stokes CFD assessment

Abstract:  Analysis of the 3D unsteady aerodynamics of a Darrieus wind turbine blade in motion  Highly spatially and temporally refined time-dependent simulations carried out with the COSA code  One month calculation time on more than 16.000 processors on a IBM BG/Q cluster  Detailed description of: tip losses, dynamic stall, vortex propagation and blade/wake interaction ACCEPTED MANUSCRIPT Energized by the recent rapid progress in high-performance computing and the growing The reported CFD results provide a valua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…The finite volume cell‐centered parallel NS CFD COSA code solves both the T D RANS and SST equations and their H B counterparts using structured multiblock grids. The discretization of the convective fluxes of both RANS and SST PDEs uses Van Leer's MUSCL extrapolations and Roe's flux‐difference splitting with Van Albada's flux limiter.…”
Section: Numerical Solutionmentioning
confidence: 99%
“…The finite volume cell‐centered parallel NS CFD COSA code solves both the T D RANS and SST equations and their H B counterparts using structured multiblock grids. The discretization of the convective fluxes of both RANS and SST PDEs uses Van Leer's MUSCL extrapolations and Roe's flux‐difference splitting with Van Albada's flux limiter.…”
Section: Numerical Solutionmentioning
confidence: 99%
“…Yanzhao Y et al [11] studied the effects of tip vortex on the wake of a two-blade VAWT with different tip speed ratios (TSRs) by CFD simulations. Balduzzi et al [12] conducted a detailed 3D CFD analysis of H-type Darrieus single-blade rotor with an aspect ratio (AR) of 17.5. Studies have shown that the torque loss caused by the three-dimensional effect due to the finite blade length is equivalent to the blade length loss of 1.5c.…”
Section: Introductionmentioning
confidence: 99%
“…3D URANS results of VAWT in skewed flows are presented in [11], 2D and 3D models are applied in [3] for aerodynamic modeling, and in [12] to investigate the self-starting capability of VAWT. The most advanced attempt of a fully 3D simulation of a VAWT is reported in [13], where a single-blade configuration was considered due to restrictions in computational cost.The present paper shows how a proper computational set-up allows obtaining reliable three-dimensional prediction of the flow around the rotor, of the wake, and of the turbine performance, at a reasonable (namely, industrially affordable) computational cost. Simulations were performed with the STAR-CCM+ commercial code, and the results were assessed against experimental data coming from a wide test campaign performed in a large-scale wind tunnel.…”
mentioning
confidence: 99%
“…3D URANS results of VAWT in skewed flows are presented in [11], 2D and 3D models are applied in [3] for aerodynamic modeling, and in [12] to investigate the self-starting capability of VAWT. The most advanced attempt of a fully 3D simulation of a VAWT is reported in [13], where a single-blade configuration was considered due to restrictions in computational cost.…”
mentioning
confidence: 99%